Training for Sustainable Workforce Development: A Systematic Literature Review in Organizational Context - Md. Imtiaz Uddin Chowdhury (Journal of Transformational Human Resource Management, 2026)
The paper “Training for Sustainable Workforce Development: A Systematic Literature Review in Organizational Context” aims to enhance the performance of an organization by reducing the disengagement of employees in departmental works. Training and development are integral to the creation and maintenance of a sustainable workforce. In today’s dynamic organizational environments, sustainability is not limited to environmental concerns; it also encompasses the long-term viability of human capital. This article explores the importance of training in promoting sustainable workforce development. It discuss on the materialistic application of different scholars’ theories of concern issues for sustainable workforce development. There have tried to make coherent the theories for SWD in organizational contexts. The paper concludes by offering strategic recommendations for integrating sustainability-oriented training programs in modern organizations. Consequently this environment uplifted management/employees skills that accelerating the organizational performance as well as establish a brand.